2022
DOI: 10.3390/ijms23031442
|View full text |Cite
|
Sign up to set email alerts
|

Male Rat Offspring Are More Impacted by Maternal Obesity Induced by Cafeteria Diet than Females—Additive Effect of Postweaning Diet

Abstract: Maternal obesity increases the risk of health complications in offspring, but whether these effects are exacerbated by offspring exposure to unhealthy diets warrants further investigation. Female Sprague-Dawley rats were fed either standard chow (n = 15) or ‘cafeteria’ (Caf, n = 21) diets across pre-pregnancy, gestation, and lactation. Male and female offspring were weaned onto chow or Caf diet (2–3/sex/litter), forming four groups; behavioural and metabolic parameters were assessed. At weaning, offspring from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…We observed that adult male offspring from HC-CP mothers had higher body weights and food intakes than offspring from CON mothers, confirming that maternal obesity can increase the risk of obesity in offspring, at least in males. This sex-specific response has been observed in some [ 45 , 46 ], but not all [ 47 , 48 ], previous rodent model studies investigating the transgenerational impact of maternal obesity. Chang et al (2019) reported that male mouse offspring born to mothers fed a high-fat diet before conception had greater weight gain and subcutaneous adipose mass compared with their female counterparts when exposed to a postnatal high-fat diet challenge [ 49 ].…”
Section: Discussionmentioning
confidence: 71%
“…We observed that adult male offspring from HC-CP mothers had higher body weights and food intakes than offspring from CON mothers, confirming that maternal obesity can increase the risk of obesity in offspring, at least in males. This sex-specific response has been observed in some [ 45 , 46 ], but not all [ 47 , 48 ], previous rodent model studies investigating the transgenerational impact of maternal obesity. Chang et al (2019) reported that male mouse offspring born to mothers fed a high-fat diet before conception had greater weight gain and subcutaneous adipose mass compared with their female counterparts when exposed to a postnatal high-fat diet challenge [ 49 ].…”
Section: Discussionmentioning
confidence: 71%
“…Full details of this cohort were reported in our previous study. [ 29 ] Briefly, females were fed Chow ( n = 15, mean weight = 213 ± 2 g [SEM]) or Caf ( n = 21, 217 ± 1 g) diets for 6 weeks, then mated with chow‐fed males. Litters were standardized to 6‐male and 6‐female pups, where possible.…”
Section: Methodsmentioning
confidence: 99%
“…*Data from siblings reported previously. [29] to the other diet (groups CCaf and CafC). At 22 weeks of age, rats in the ChowCaf and CafCaf groups were switched to the chow diet for a further 5 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of developmental programming due to maternal obesity differs by sex of the offspring in rodent models. Male offspring, compared to female offspring, show greater body weight, retroperitoneal fat mass, liver mass, plasma leptin levels, and impaired glucose tolerance [ 87 , 88 ]. Furthermore, male offspring have decreased islet number and secretion at postnatal day 21 compared to female offspring [ 89 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%